Supporting data for 'An insight into the hormonal interplay regulating pigment changes and colour development in the peel of ‘Granny Smith’, ‘Opal®’ and ‘Royal Gala’ apples' - Alamar, M. Carmen; Teixidó, Neus; Giné-Bordonaba, Jordi; Fernández Cancelo, Pablo (Cranfield University, 2024)
This data set contains physiological (colour, size, total soluble content) and biochemical data (including plant hormones, indivicual sugars, anthocyanins) of three different apple cultivars. It also includes the gene expression of gene involved in the ethylene pathway.
Keywords: Abscisic acid (ABA)'; 'anthocyanins Anthocyanin biosynthesis'; 'Carotenoids metabolism'; 'ethylene'